ANALISIS FAKTOR KETERLAMBATAN PROYEK PEMBANGUNAN GEDUNG AGRARIA DAN TATA RUANG BADAN PERTANAHAN BOJONEGORO TAHAP II - Carina, Annisa’; Rabbani, Anggitsna Mujib; Lestari, Fitria Maya; Fahrurroziqin, Nor Ahmad; Ramadhan, Khozin Gilang; Kristiawan, Agung (Jurnal Teknik Sipil Giratory UPGRIS, 2026)
Construction project delays are a common problem in Indonesia, often resulting in increased costs, decreased quality, and disruption to project completion schedules. This study aims to analyze the factors causing delays in the Bojonegoro Land Agency's Agrarian and Spatial Planning Building Phase II project. The Critical Path Method (CPM) was used, which identifies the critical path within the project and activities that could potentially cause delays. Data were collected through documentation,  field observations, and interviews with project stakeholders. The results indicate that delays occurred due to several internal factors, such as inexperienced workers, delays in the provision  of materials  and equipment,  and  ineffective  coordination.  The project's critical path consists of a series of activities with no time leeway (float) with a total duration of 108 days. By understanding the activities on the critical path, project managers can take mitigating measures to prevent further delays. This study contributes to construction project time management and serves as a reference for future similar research.